Localizing The Qur’an in Javanese Pesantren: A Socio-Cultural Interpretation of Al-Ibrīz and Al-Iklīl - Baidowi, Ahmad; Ma’rufah, Yuni (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
The production of Javanese Qur’anic commentaries in Pegon script within the pesantren (Islamic boarding school) tradition reflects the authors varying degrees of engagement with the socio-cultural realities of Javanese society. This paper investigates the influence of socio-cultural factors in Al-Ibrīz li Ma’rifat Tafsīr al-Qur’ān al-‘Azīz by Bisri Mustafa from Pesantren Raudhatut Thalibin (Rembang, Central Java), and Al-Iklīl fī Ma’ānī al-Tanzīl by Misbah Mustafa from Pesantren Al-Balagh (Tuban, East Java). Adopting a descriptive-analytical method, this study explores how both authors responded to socio-cultural phenomena or offered culturally grounded interpretations in their tafsir works. Their use of local knowledge and their responses to cultural practices are analyzed through content analysis to determine their interpretive orientations—whether leaning toward Arabization, Islamization, or localization. The findings reveal that both authors utilize local knowledge to explicate Qur’anic meanings. In responding to social phenomena, they adopt two main approaches: critical evaluation and selective accommodation of cultural practices. This study affirms the dynamic intellectual engagement of pesantren kiais in contextual Qur’anic interpretation.